Antara Domestik Dan Publik : Peran Gender Polisi Wanita di Kepolisian Resor Sumba Timur - Dila Rebeka Djoh; Rambu Luba Kata Respati Nugrohowardhani (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study explores how policewomen (Polwan) at the East Sumba Police Resort (Polres Sumba Timur) manage dual roles—as law enforcers in the public sphere and as wives and mothers within the domestic sphere. A qualitative method was employed, using data collection techniques such as field observation, in-depth interviews, and document analysis. The findings reveal that Polwan are capable of balancing their professional and familial responsibilities, despite facing challenges such as demanding work schedules, psychological stress, and limited institutional support. To overcome these obstacles, they adopt strategies such as effective time management, maintaining open communication with family members, and seeking moral support from colleagues. Overall, the study shows that policewomen possess strong adaptive capabilities in fulfilling their dual roles and contribute positively to the advancement of women's roles in public institutions. These findings are expected to inform the development of more inclusive and gender-responsive policies within the police force.